Impact of Periosteal Branches and Septo-Cutaneous Perforators on Free Fibula Flap Outcome: A Retrospective Analysis of Computed Tomography Angiography Scans in Virtual Surgical Planning - Knitschke, Michael; Baumgart, Anna Katrin; Bäcker, Christina; Adelung, Christian; Roller, Fritz; Schmermund, Daniel; Böttger, Sebastian; Streckbein, Philipp; Howaldt, Hans-Peter; Attia, Sameh (Frontiers in Oncology, 2022)
Background Virtual surgical planning (VSP) for jaw reconstruction with free fibula flap (FFF) became a routine procedure and requires computed tomography angiography (CTA) for preoperative evaluation of the lower limbs vascular system and the bone. The aim of the study was to assess whether the distribution and density of periosteal branches (PB) and septo-cutaneous perforators (SCP) of the fibular artery have an impact on flap success. Method This retrospective clinical study assessed preoperative CTA of the infra-popliteal vasculature and the small vessel system of 72 patients who underwent FFF surgery. Surgical outcome of flap transfer includes wound healing, subtotal, and total flap loss were matched with the segmental vascular supply. Result A total of 72 patients (28 females, 38.9 %; 44 males, 61.1 %) fulfilled the study inclusion criteria. The mean age was 58.5 (± 15.3 years). Stenoses of the lower limbs’ vessel (n = 14) were mostly detected in the fibular artery (n = 11). Flap success was recorded in n = 59 (82.0%), partial flap failure in n = 4 (5.5%) and total flap loss in n = 9 (12.5%). The study found a mean number (± SD) of 2.53 ± 1.60 PBs and 1.39 ± 1.03 SCPs of the FA at the donor-site. The proximal FFF segment of poly-segmental jaw reconstruction showed a higher rate of PB per flap segment than in the distal segments. Based on the total number of prepared segments (n = 121), 46.7% (n = 7) of mono-, 40.4% (n = 21) of bi-, and 31.5 % (n = 17) of tri-segmental fibula flaps were at least supplied by one PB in the success group. Overall, this corresponds to 37.2% (45 out of 121) of all successful FFF. For total flap loss (n = 14), a relative number of 42.9% (n = 6) of distinct supplied segments was recorded. Wound healing disorder of the donor site was not statistically significant influenced by the detected rate of SCP. Conclusion In general, a correlation between higher rates of PB and SCP and the flap success could not be statistically proved by the study sample. We conclude, that preoperative PB and SCP mapping based on routine CTA imaging is not suitable for prediction of flap outcome.